Nowoczesne czytanie Leśmiana - Larek, Michał (Poznańskie Studia Polonistyczne. Seria Literacka, 2009)
The text discusses critically the analyses of Leśmian’s poems carried out by Markowski in his Polska literatura nowoczesna [Polish modern literature]. The critical evaluation focuses on the following four key assumptions (and convictions) presented by Markowski: 1. literature is an epistemological and educational task that aims at promoting and teaching critical thinking; 2. the history of literature involves permanent re-rendering of interpretative techniques; 3. literary text is ambiguous because it cannot be generalized and is a record of human experience, both existentialist and intellectual; 4. interpretation should testify to the idiomatic nature of the text. In the course of reading the book, however, it turns out that on more than one occassion Markowski is inconsistent and even contradicts himself. As a result, he lays himself open to charges suggesting that he does not consistently stick to his methodological postulates, sometimes even contradicting them. The article is concluded with a suggestion that the image of the literary critic as a diligent deconstructionist is badly shaken. Markowski is more interested in philosophical aspects in a literary work than in its aesthetical value. The text represents thus a revisionist and debunking contribution to the readings of this “harbinger of postmodernity”.